Assessment of in Vitro Comparative Dissolution Kinetics of Moxonidine Products as a Factor Potentially Determining Effectiveness of Antihypertensive Treatment - G. V. Ramenskaya; I. E. Shokhin; N. I. Gaponova; V. R. Abdrakhmanov (Столичная издательская компания, 2019)
Aim. Investigation of comparative dissolution kinetics of generic medicinal products containing moxonidine versus reference drug. Material and methods. Objects of the research were film-coated tablets containing moxonidine (INN) in a dose 0.4 mg: a reference drug Physiotens® and 4 generic drugs. In vitro dissolution test of moxonidine from the study drugs was performed using comparative dissolution kinetics test (CDKT). The CDKT was performed in the media with the following pH: 1.2 (1:9 mixture of 0.1 M hydrochloric acid and water), 4.5 (acetate buffer solution, prepared as per State Pharmacopoeia, XIII), and 6.8 (phosphate buffer solution, prepared as per State Pharmacopoeia, XIII). The sampling for dissolved moxonidine was performed 5, 10, 15, 20, and 30 min after the test was started. An high performance liquid chromatography method with ultraviolet detection at 220 nm was used to assay. Results. Within 15 min more that 85% of moxonidine dissolved from the reference drug and all study drugs at pH 1.2; dissolution profiles were similar without calculation of similarity factor f2. Similarly, at pH 4.5 dissolution profiles of study drugs #2 and #3 were similar to that of the reference drug, and the similarity factor f2 was not calculated. However, in case of study drugs #1 and #4 significant differences were observed at a single time point (15 min), which suggests that their dissolution profiles are non-similar to that of the reference drug. Similarity factors f2 were calculated 17.52 and 35.30, respectively (less than 50). At pH 6.8 similarity factors f2 for all study generic drugs were also less than 50 (23.8, 49.8, 38.6, and 35.9), so their dissolution curves were non-similar to that of reference drug. Conclusion. In our study we observed difference in release in vitro of medicinal products containing moxonidines: none of the study drugs was fully similar to the reference drug in all media. The differences observed at pH 6.8 were noteworthy, where the samples had or faster kinetics (study drugs #2 and #3), or slower dissolution kinetics (test drugs #1 and #4). Observed differences in moxonidine release rate may impact absorption of active pharmaceutical ingredient into the blood following drug administration.